In-situ formation of mesoporous SnO2@C nanocomposite electrode for supercapacitors. (1st January 2021) - Rani, Malothu Usha; Naresh, Vangapally; Damodar, Devarakonda; Muduli, Sadananda; Martha, Surendra Kumar; Deshpande, Atul Suresh
Highlights: One-pot synthesis of mesoporous SnO2 @C composite is achieved using polymer beads. Interconnected porous structure allows full accessibility of electrolyte ions to SnO2 . It exhibits high specific capacitance of 432 F g −1 at 1 Ag −1 in aqueous electrolyte. Achieved high energy density of 29.4 Wh kg −1 and power density of 418 W kg −1 . 95.5% of initial capacitance retained after 2000 cycles at 2 A g −1 current density. Abstract: In this work, we report a supercapacitor based on SnO2 @C composite electrode with better electrochemical performance. SnO2 @C composite is synthesized from porous polymer beads by the impregnation method. The resultant composite is porous and retains uniform spherical morphology of polymer beads. The composite exhibits the bimodal distribution of pores with a specific surface area of 286 m 2 g −1 . SnO2 @C composite electrode show specific capacitance of 432 F g −1 at 1 A g −1 in 1M KOH electrolyte with capacitance retention of 95.5% for 2000 cycles. Besides, the composite electrode shows an energy density of 29.4 Wh kg −1 at a power density of 418 W kg −1 at 1 A g −1 current density. The optimize electrode design improves cyclic stability due to reducing crystal growth of SnO2 as well as diffusion kinetics because of the presence of bimodal pores which provides continuous electron path. The bimodal micropores and mesopores in carbon matrix have the accessibility of electrolyte to SnO2, improving overall electrochemical performance and therefore SnO2 @C composite is suitable as electrode material for supercapacitors. Graphical abstract: Image, graphical abstract